Strain assessment in the carotid artery wall using ultrasound speckle tracking: validation in a sheep model. (13th January 2015) - Larsson, Matilda; Verbrugghe, Peter; Smoljkić, Marija; Verhoeven, Jelle; Heyde, Brecht; Famaey, Nele; Herijgers, Paul; D'hooge, Jan
Abstract: The aim of this study was to validate carotid artery strain assessment in-vivo using ultrasound speckle tracking. The left carotid artery of five sheep was exposed and sonomicrometry crystals were sutured onto the artery wall to obtain reference strain. Ultrasound imaging was performed at baseline and stress, followed by strain estimation using an in-house speckle tracking algorithm tuned for vascular applications. The correlation between estimated and reference strain was r = 0.95 ( p  < 0.001) and r = 0.87 ( p  < 0.01) for longitudinal and circumferential strain, respectively. Moreover, acceptable limits of agreement were found in Bland–Altman analysis (longitudinally: −0.15 to 0.42%, circumferentially: −0.54 to 0.50%), which demonstrates the feasibility of estimating carotid artery strain using ultrasound speckle tracking. However, further studies are needed to test the algorithm on human in-vivo data and to investigate its potential to detect subclinical cardiovascular disease and characterize atherosclerotic plaques.